Endogenous ocular lipids as potential modulators of intraocular pressure. Issue 7 (23rd February 2020) - Edwards, Genea; Arcuri, Jennifer; Wang, Haiyan; Ziebarth, Noel; Zode, Gulab; Lee, Richard K.; Bhattacharya, Sanjoy K.
Abstract: Elevated intraocular pressure (IOP) is a risk factor in glaucoma, a group of irreversible blinding diseases. Endogenous lipids may be involved in regulation of IOP homeostasis. We present comparative fold analysis of phospholipids and sphingolipids of aqueous humour and trabecular meshwork from human control vs primary open‐angle glaucoma and mouse control (normotensive) vs ocular hypertensive state. The fold analysis in control vs disease state was based on ratiometric mass spectrometric data for above classes of lipids. We standardized in vitro assays for rapid characterization of lipids undergoing significant diminishment in disease state. Evaluation of lipids using in vitro assays helped select a finite number of lipids that may potentially expand cellular interstitial space embedded in an artificial matrix or increase fluid flow across a layer of cells. These assays reduced a number of lipids for initial evaluation using a mouse model, DBA/2J with spontaneous IOP elevation. These lipids were then used in other mouse models for confirmation of IOP lowering potential of a few lipids that were found promising in previous assessments. Our results provide selected lipid molecules that can be pursued for further evaluation and studies that may provide insight into their function.